Avaliação do ciclo de vida de fundações de torres eólicas: Estudo Comparativo - Barroso, Ana Paula de Morais (2023)
Recently wind energy has been considered one of the most environmentally promising. Despite their renewable nature, non-renewable resource inputs and greenhouse gas emissions occur during the life cycle of these systems. The Life-Cycle Assessment (LCA) methodology makes it possible to quantify the possible environmental impacts of a product or system. LCA studies for wind towers usually detect the foundation of the tower as the component with the highest environmental impact. In this context, a new model of wind tower stands out based on the tensegrity system, called ''wind tower'', which differs from the current systems used in the lower section of the tower and in the foundation, drastically reducing the volume of concrete and the amount of steel reinforcement used in the foundations, enabling the reduction of materials, transport, costs and, evidently, the environmental impact. Thus, the objective of this dissertation was to carry out a comparative LCA between three types of foundation: standard shallow foundation, standard deep foundation and the tensegrity foundation for a hypothetical wind turbine located in the Northeast region of Brazil. To perform the LCA, the systems were analyzed using the OpenLCA software, for six midpoint impact categories in the IMPACT 2002+ method: Non-renewable energy, Global warming, Mineral extraction, Terrestrial acidification, Land occupation, Terrestrial ecotoxicity. In short, the tensegrity foundation showed significant reductions in impacts in all evaluated categories. It was also evident that in standard foundations, concrete was responsible for a significant portion of the environmental impacts, contributing with about 59% of the impacts in the shallow foundation and 50% in the deep foundation. Since concrete and transport distances are the items with the biggest contributions to the total impact, and consequently, which promote greater variability in the results, a sensitivity analysis was performed for these items. The analysis has shown that the search for cement control in the mixtures, through the use of cementitious materials and the reduction of transport distances are excellent measures to reduce the impacts.